An Overview of RNA Sequence Analyses: Structure Prediction, ncRNA Gene Identification, and RNAi Design. Issue 1 (16th February 2018) - Stormo, Gary D.
Abstract: This unit briefly describes the two fundamentally different methods for predicting RNA structures. The first is to find that structure with the minimum free energy of folding, as predicted by various thermodynamic parameters related to base‐pair stacking, loop lengths, and other features. If one has only a single sequence, this thermodynamic approach is the best available method. The second fundamental approach to RNA structure prediction is to use multiple, homologous sequences for which one can infer a common structure, and then try and predict a structure common to all of the sequences. Such an approach is referred to as a comparative method or phylogenetic method of RNA structure prediction. Curr. Protoc. Bioinform . 43:12.1.1‐12.1.3. © 2013 by John Wiley & Sons, Inc.